INVESTMENT ATTRACTIVENESS: PERAN MODERASI REPUTASI PERUSAHAAN TERHADAP HUBUNGAN ESG PERFORMANCE DAN KEUNGGULAN KOMPETITIF - Putri Dwi Wahyuni; Fitri Indriawati; Feber Sormin; Asep Husni Yasin Rosadi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study addresses the issue of investment attractiveness on the Indonesia Stock Exchange (IDX) by highlighting Environmental, Social, and Governance (ESG) performance and corporate competitive advantage. The main problem lies in the low level of ESG strategy integration in Indonesian companies, even though global investors are increasingly emphasising sustainability in their investment decisions. The purpose of this study is to analyse the effect of ESG performance and competitive advantage on investment attractiveness and to examine the role of corporate reputation as a moderating variable. The research method uses a quantitative approach with secondary data from 57 non-financial companies listed on the IDX for the period 2021–2023. The analysis was conducted using Moderated Regression Analysis (MRA) with EViews 10 software. The novelty of this study lies in the use of corporate reputation with CSR Strategy Score measurement as a moderating variable, which has rarely been examined in previous studies. The results show that ESG performance does not have a significant effect on investment attractiveness, while competitive advantage has a significant negative effect. However, when corporate reputation is included as a moderator, the relationship between ESG and competitive advantage on investment attractiveness becomes significant, confirming the importance of reputation as a reinforcing mechanism. These findings are expected to contribute to companies and regulators in designing more effective sustainability strategies.